Formulasi, Evaluasi dan Penentuan Nilai SPF Serta Uji Kelembaban Perona Pipi Stik Ekstrak Etanol Bawang Dayak (Eleutherine bulbosa (Mill.) Urb - Hutagalung , Septi Ratna Cempaka; Yuniarti , Rafita; Dalimunthe , Gabena Indrayani; Lubis , Minda Sari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Blush is traditionally used to add color to cheeks, but UV exposure poses significant skin damage risks. Dayak onion (Eleutherine palmifolia), containing anthocyanins as natural pigments and photoprotective compounds, shows potential as a multifunctional blush ingredient. Objectives: The aim of this study is to determine whether Bawang Dayak can be formulated as a natural colorant for blushers, whether Bawang Dayak extract possesses sun protection properties, and whether the ethanol extract of Bawang Dayak blusher has sun protection and skin moisturizing abilities. Methods: An experimental study employing quantitative and qualitative approaches was conducted. The research stages included material characterization, phytochemical screening, SPF testing of extract and formulations, physical quality evaluation (homogeneity, stability, adhesiveness), and in vivo skin hydration testing. Ethanolic Dayak onion extract samples were prepared at varying concentrations (100-1000 ppm). Results: The ethanolic extract was successfully formulated into stick blush meeting standard physical quality criteria. The extract demonstrated ultra SPF ratings (1000 ppm: SPF 32; 700 ppm: SPF 25; 500 ppm: SPF 21) to minimal protection (100 ppm: SPF 4). The 1000 ppm blush formulation showed ultra SPF 29, while the 700 ppm formula (F2) exhibited the highest skin moisturizing capacity. Conclusion: Dayak onion shows promise as both a natural colorant and active sunscreen agent in blush formulations. The developed product meets physical quality standards while offering dual functionality as a color cosmetic with UV protection.